High-Temperature Oxidation Performance of 4Cr4Mo2NiMnSiV Hot Die Steel - Renheng HAN (Kaunas University of Technology, 2021)
A new type of hot working die steel was designed by using JMatPro, and high-temperature oxidation tests were carried out in the ambient atmosphere at 600 ℃ and 700 ℃. The heat treatment process and oxidation mechanism of the designed 4Cr4Mo2NiMnSiV steel were studied in detail. XRD, SEM and EDS were used to analyze the crystallographic phases, surface and cross-section morphologies of the oxide films. The results show that the main phases in the 4Cr4Mo2NiMnSiV steel were γ and α + δ. During the high-temperature oxidation, oxidation of the Fe outer layer and Cr inner layer occurred. After oxidation at 600℃, the surface oxidation layer comprised a monolayer with an uneven morphology. The surface oxide film had two layers after oxidation at 700℃. The outer oxide layer mainly contained Fe2O3 and Fe3O4, while the inner oxide layer mainly contained Cr2O3. The microstructure was relatively regular and had a significant effect on the protection of the metallic matrix. When oxidized, the 4Cr4Mo2NiMnSiV alloy steel easily formed protective layers, such as Cr2O3 and SiO2, so that the test steel had excellent oxidation resistance at high temperatures.